Fine tuning enzyme activity assays for monitoring the enzymatic hydrolysis of PET - Krisztina Boros; Blanka Eszter Nagy; Raluca Bianca Tomoiagă; Róbert Tőtős; Monica Ioana Toșa; Csaba Paizs; László Csaba Bencze (Scientific Reports)
Abstract Efficient monitoring of the enzymatic PET-hydrolysis is crucial for developing novel plastic-degrading biocatalysts. Herein, we aimed to upgrade in terms of accuracy the analytical methods useful for monitoring enzymatic PET-degradation. For the HPLC-based assessment, the incorporation of an internal standard within the analytic procedure enabled a more accurate quantification of the overall TPA content and the assessment of molar distributions and relative content of each aromatic degradation product. The provided calibration curves cover a broad concentration range, from µM to low mM scale, facilitating assessment of both lower and higher PETase activities, with a limit of detection positioned below the reported PET-degrading activities. The increased reproducibility and accuracy of the improved HPLC method, compared to the previous methods, was supported by lower dispersion of product concentrations and their lower deviation from theoretical values over multiple measurements. The other predominantly employed UV-spectroscopy assay was also improved in terms of employed wavelength and medium extinction coefficient of the three aromatic degradation products, while being cross-validated by the improved HPLC method. Finally, both methods were used for monitoring the product formation within the leaf-branch compost cutinase (LCC)-mediated PET-hydrolysis and provided individual time-productivity profiles for each aromatic degradation product.